Mangrove Class: Field Experience-Based Education for Coastal Ecosystem Conservation in Wedung, Demak - Wulandari, Cahyo; Salsabila, Gesti Nola; Siami, Eni Nur; Marwadani, Laila Mei (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Mangrove ecosystems play an essential role in sustaining coastal environments through their ecological, economic, and social functions, such as serving as natural coastal protection, providing habitats for various biota, and supplying sources of livelihood. However, in the coastal area of Wedung, Demak, knowledge of the community for the functions and benefits of mangroves remains low, despite the significant and abundant potential of this ecosystem. The Mangrove Class, community service program, implemented by the KKN-PPM UGM team, aimed to introduce and enhance awareness, care, and involvement of SMPN Satu Atap Wedung, Demak students in mangrove conservation efforts. The implementation method included problem observation and environmental surveys, planning, coordination and discussions with the school, program execution, and reporting and evaluation. Activities were designed to be interactive and experiential, combining classroom education with direct field learning. The program series included classroom lessons on coastal and marine ecosystems, field introduction to various mangrove species along with their characteristics and benefits, simple herbarium creation, and the planting of 1,000 mangrove propagules held in conjunction with World Mangrove Day. Participant enthusiasm was evident from their active engagement in all activities, including their ability to answer oral interactive quizzes, indicating comprehension of the materials presented. Students were also able to accurately describe several mangrove species they encountered in the field based on simple identification they had conducted. The program received positive responses from the school, teachers, and the community, who regarded it as an innovative environmental learning initiative relevant to the local context. Therefore, this community service program is worth replicating, as it integrates environmental education with conservation actions in coastal areas, using mangrove planting as a strategy to strengthen awareness, care, and community involvement in preserving ecosystems and ensuring environmental sustainability.